Ocriplasmin for Treatment of Vitreomacular Traction: An Update. Issue 2 (December 2016) - Khan, Mohammed; Haller, Julia
Abstract Pharmacologic vitreolysis with ocriplasmin, a 27 kilodalton serine protease, is an effective nonsurgical treatment option for vitreomacular traction (VMT). Data from phase III clinical studies, including the Microplasmin for Intravitreal Injection—Traction Release without Surgical Treatment (MIVI-TRUST) and Ocriplasmin for Treatment for Symptomatic Vitreomacular Adhesion Including Macular Hole (OASIS) studies, have demonstrated the treatment efficacy of ocriplasmin for VMT and full-thickness macular hole (FTMH). Subgroup analysis of these clinical trials as well as post-marketing clinical series have aided in patient selection by identifying features associated with successful pharmacologic release of VMT with ocriplasmin, including adhesion diameter ≤1500 μm, absence of epiretinal membrane, phakic status, and age younger than 65. As a first-in-class therapeutic, ocriplasmin and its side effects have been carefully monitored by the vitreoretinal community. The following categories of related or possibly related adverse events have been identified: acute reduction in visual acuity, ERG changes, dyschromatopsia, retinal tear or detachment, lens subluxation or phacodonesis, abnormal pupillary reflex, retinal vascular changes, and OCT ellipsoid zone alterations. Adverse events have almost all been transient with restoration of visual acuity; however, in select patients, alterations may persist.